Water and electric utility integrated planning: Joint Utility Planning Tournament: summary report - Conrad, Steven A., author; Kenway, Steven J., author; Jawad, Maria, author; Water Research Foundation, publisher (Colorado State University. Libraries, 2015)
This report summarizes the Water and Electric Utility Integrated Planning: Joint Utility Planning Tournament held in Denver, Colorado, on October 16–17, 2014. The event brought together 32 participants from the United States, Canada, and Australia, including representatives from water and electric utilities, regulatory agencies, academia, and related professional sectors. Through a simulated planning exercise set in the fictional city of Meadowlands, five teams developed and defended long-term integrated plans in response to two management scenarios. Plans were evaluated on their ability to address cross-sector needs, manage vulnerabilities and conflicts, improve system reliability and adaptability, and enhance customer service. The tournament revealed both significant opportunities and persistent barriers to integrated water and electric utility planning. Participants found the format effective for highlighting differing sector perspectives, terminology, and service goals. Major barriers identified included incompatible political and regulatory frameworks, siloed institutional cultures, and limited public and sector-wide awareness of the water-energy nexus. Water and electricity were also seen as carrying different social and environmental meanings, further complicating coordinated planning. Despite these challenges, participants identified several promising areas for collaboration, including efficiency improvements, watershed management, hydroelectric generation, and water demand management. Additional benefits of joint planning included potential cost savings, stronger resilience to future uncertainties, increased customer awareness of water-energy interdependencies, and greater potential for innovation and sustainable cross-sector solutions. Overall, the tournament demonstrated that integrated planning can provide meaningful strategic value, but broader institutional alignment and awareness are needed to advance it in practice.
Joint Utility Planning Tournament: summary report
Authors supplied by Steve Conrad, a CSU faculty member.
Keywords: water-energy nexus; water and electric utility planning; utility resilience; cross-sector infrastructure planning; serious gaming; simulation-based planning